Synthetic anticonvulsants, antihypoxics, and liver monooxygenase system inducers based on amides and urea; V; Synthesis and anticonvulsive and antihypoxic activities of 1,3 dibenzhydrylureas; Pharmaceutical Chemistry Journal; Vol. 27, iss. 4 - Bakibaev A. A. Abdigali Abdimanapovich; Gorshkova V. K.; Shtrykova V. V. Viktoriya Viktorovna; Saratikov A. S.; Filimonov V. D. Viktor Dmitrievich; Krauin'sh M. P. (1993, 1993)
Title screen